The pressure treatment effect on the high‑strength austempered ductile iron structure - P. E. Lushchik; A. I. Pokrovsky; I. V. Rafalsky; A. D. Rulenkov (Литьë и металлургия, 2024)
This paper presents the results of a study on the effect of pressure treatment (direct hot extrusion) on the structure of graphite inclusions and the metallic matrix of high‑strength austempered ductile iron. Comparative analysis of the cooling processes of the cast high‑strength ductile iron billet without deformation and after deformation was carried out using simulation modeling methods. The results of the study on the effect of hot deformation (up to 950–970 ℃) on the fracture structure and mechanical properties of austempered high‑strength ductile iron billets are presented.